Integrative Perspectives on Relapse in Addiction: A Comparative Analysis of Contemporary Clinical Models and Ayurvedic Interventions - Pipavat, Darsh Kishorbhai; Devidas Namewar, Prasad (Journal of Neonatal Surgery, 2025)
Relapse is generally defined as the return to substance use after a period of abstinence, effectively interrupting progress in recovery. In addiction medicine, relapse is viewed as a dynamic, ongoing process rather than a single event. In practice, it may begin with an emotional relapse (growing stress or cravings), followed by a mental relapse (internal struggle), and culminate in a physical relapse when use resumes. Relapse is common in addiction: for example, the National Institute on Drug Abuse (NIDA) reports relapse rates for treated substance disorders are comparable to those for chronic illnesses like hypertension or asthma. Studies worldwide show that 40–60% of treated patients relapse after detoxification and rehabilitation, and even 80–95% relapse after tobacco or alcohol cessation attempts without ongoing support. Behavioral addictions (e.g. gambling, internet use) likewise exhibit high relapse rates, as they share similar neurological pathways of craving and reinforcement. Indeed, relapse has been called “the biggest problem” for recovering addicts. Understanding relapse its definition, patterns, and frequency is therefore crucial in all domains of addiction (substance and behavioral